Avaliação experimental do comportamento mecânico de dormentes reciclados de madeira visando redução do impacto ambiental - Leonardo Braga Passos (2006)
Nowadays due to environmental worry with the high deforestation and the high sleeper costs, the railroad industry has decreased drastically the use of native wooden sleepers. Thus, other materials such as steel, concrete, polymers and reforestation wood (Eucalyptus) have been used in the railway sleeper production. With the purpose of decreasing the environmental impact, a recycling project has been proposed wherewaste wooden sleepers, that usually have been discarded or then, have been sold by the railroad operations with low price, now will be transformed into glulam sleepers. This work provides all the manufacture stages of recycling glulam sleepers and eucalyptus; The procedure for determination of the elastic modulus through the ultrasonic method ispresented with the aim of classifying the wood pieces to improve the sleeper strength; The results of two statistical testing methods accomplished in testing Laboratory and its comparison with the numerical simulation results obtained through the use of ANSYSversion 9.0 software. It has been verified that for the displacement studies, the dynamic loading test is most suitable and for the tension deformation studies, the static loading test according to NBR12131 (ABNT, 1992). In addition to the static loading tests, one of the recycling glulam sleepers has been installed in the railway network of FerroviaCentro Atlântica that belongs to Companhia Vale do Rio Doce with the purpose of monitoring the strains and accelerations suffered by this sleeper. For these testings it has been carried out just a simplified study, however, it has presented astonished results. The main conclusion is thats possible to obtain a wooden sleeper through the recyclingof five waste sleepers, thus, as a result, it will have a significant environmental impact decrease